Chronomics and Continuous Ambulatory Blood Pressure Monitoring : Vascular Chronomics: From 7-Day/24-Hour to Lifelong Monitoring /: Vascular Chronomics: From 7-Day/24-Hour to Lifelong Monitoring. (2016) - Otsuka, Kuniaki; Cornelissen, Germaine; Halberg, Franz
No abstract available